Desarrollo de aplicaciones Restful transaccionales en Scala y el Framework Play (2017)
The emergence of new technologies such as the cloud, brings new opportunities and challenges to the industry related to processing, scalability, performance and availability. In addition to this, new alternatives appear as a way to solve such challenges. Scala, as a programming language, provides new features with a functional and object-oriented approach, capable of operating with the java virtual machine (JVM) and designed with the premise of facilitating the scalability of the applications, a feature imperative to environments with multiple processors and cores such as the cloud. Similarly, the Play framework surges as a reactive alternative claiming to provide better performance and resource administration. The following document describes the characteristics and features that Scala and the Play framework provide in the development of transactional applications. It is oriented and supported by the description and development of an application with the basic CRUD functionalities that follows and guarantees a set of quality attributes critical for any business domain that wants to deploy its applications to the cloud.--Tomado del Formato de Documento de Grado.